Family Function Support and Quality of Life For Breast Cancer Survivors - Hasnida Hasnida (Universitas Aisyah Pringsewu, 2021)
Post-treatment care and ongoing care plans for breast cancer sufferers can reduce the quality of life. Breast cancer patients who are hospitalized have negative factors, such as being away from their family and loved ones, unfamiliar hospital environment, getting diagnosis and treatment that is difficult so that the patient feels afraid of every procedure that will be given to him and makes quality his life was getting low. This study aims to identify the domains of quality of life in breast cancer patients. This study uses a type of correlation research with the sampling technique in this study using purposive sampling. The number of samples was 40 respondents in the age range 24-68 years. This study used a family function support instrument and WHO QoL BREF. Based on the results of the Fisher exact test, the four family functions showed a significant relationship to the quality of life of the study subjects with a p-value less than 0.001. The protection function showed the greatest impact in affecting the quality of life of the subjects with OR = 41,600 (95% CI = 4,219-410,222). The function of love shows OR = 6,400 (95% CI = 2,861-14,317), the economic function shows OR = 5,500 (95% CI = 2,667-11,342), and the religious function with OR = 4,857 (95% CI = 2,510-9,399). Therefore, it is very important that the family can provide support for the protective function of breast cancer survivors.Perawatan pasca pengobatan dan rencana perawatan berkelanjutan penderita kanker payudara dapat menurunkan kualitas hidup. Pasien kanker payudara yang dirawat di rumah sakit memiliki faktor negatif, seperti jauh dari keluarga dan orang-orang yang dicintainya, lingkungan rumah sakit yang tidak dikenal, mendapatkan diagnosis dan perawatan yang sulit sehingga membuat pasien merasa takut setiap prosedur yang akan diberikan kepadanya serta membuat kualitas hidupnya semakin rendah. Penelitian ini bertujuan untuk mengidentifikasi domain dalan kualitas hidup pada penderita kanker payudara. Penelitian ini menggunakan jenis penelitian Korelasi dengan teknik pengambilan sampel dalam penelitian ini menggunakan purposive sampling. Jumlah sampel adalah 40 responden dalam rentang usia 24-68 tahun. Penelitian ini menggunakan instrument dukungan fungsi keluarga dan WHO QoL BREF. Berdasarkan hasil uji fisher exact tes, ke empat fungsi keluarga menunjukkan hubungan yang signifikan terhadap kualitas hidup subyek penelitian dengan p value kurang dari 0,001. Fungsi perlindungan menunjukkan dampak yang paling besar dalam mempengaruhi kualitas hidup subyek dengan OR=41,600 (95% CI= 4,219-410,222). Fungsi cinta kasih menunjukkan OR=6,400 (95% CI= 2,861-14,317), fungsi ekonomi menunjukkan OR=5,500 (95% CI= 2,667-11,342), dan fungsi keagamaan dengan OR= 4,857 (95% CI= 2,510-9,399). Oleh Karena itu sangat penting keluargga dapat memberikan dukungan fungsi perlindungan kepada survivor kanker payudara.